PEMBELAJARAN INTERAKTIF BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) DALAM MATERI VERTEBRATA PADA SISWA MA MUHAMMADIYAH 1 MALANG - Nurisma Afifatun Nisa; Roimil Latifa; Moch. Agus Krisno Budiyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2015)
PEMBELAJARAN INTERAKTIF BERBASIS ICT (INFORMATION AND COMMUNICATION TECHNOLOGY) DALAM MATERI VERTEBRATA PADA SISWA MA MUHAMMADIYAH 1 MALANG Nurisma Afifatun Nisa1, Roimil Latifa1, Moch. Agus Krisno Budiyanto1 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail: biologi.umm@gmail.com ABSTRAK The development of ICT in Indonesia increasing along with the time passed by. Hopefully little by little the teacher start to accustomed to used ICT based learning to adapt with the mushroom growth of time mowdays. Interactive learning media based on ICT hopefully be able to help students in comprehend the difficult materials which complicates to be mastered by the students especially in vertebrate material. In this interactive learing media development research at vertebrate material serve the purpose of learning media for student and teacher to facilitate teacher in deliver the material, also the researcher be able to know the usage of interactive learning media based on ICT in the effectiveness of student learning. This research codunsted at 10 March 2013 until 19 Octobeer 2013 in MA Muhammadiyah 1 Malang. The result of this development is produce interactive learning media product based on ICT (Information and Communication Technology) that have been made.which is had pass through testing process and revised based on suggestion and input from material expert and media expert also comment from the trial run student. Student learning activity getting off the ground from dependent class to independent class. The effectiveness of learning result and process in interactive learning media development based on ICT to increasing student achievement grade X student of MA Muhammadiyah 1 Malang getting off the ground based the data that have been obtained. Kata kunci: Vertebrate, Interactive Learning Media, ICT (Information and Communication Technology)